Le cadre éristique du débat argumentatif - Gilles Gauthier (Communication)
The author claims that public debates are no longer authentic argumentative exchanges because of the eristic frame in which they are held. The concept is borrowed from Schopenhauer but given a wider extension than that of a discursive process. With the aid of the Quebecois debate on secularism, six constituents of the extended concept of eristic are identified and analyzed : the intensification of a superficial or marginal opposition, the wording of the question, murky theorization, one’s positioning with regard to one’s opponent, the use of strategic arguments and the taking into account of peripheral contextual elements.